Isolation and Identification of Four High Glycosidase-producing Strains from Xinhuichenpi and Their Probiotics Properties and Fermentation Effect Analysis - Fei SHEN; Tingyu WANG; Hui SUN; Zhenqiang WU (Shipin gongye ke-ji)
To expand the probiotic germplasm resources for promoting the fermentation and aging of Xinhuichenpi (XHCP), four strains from XHCP were isolated and identified, and evaluated from the perspective of their enzyme-producing capabilities, probiotic characteristics, safety, and XHCP fermentation effect. All four strains belonged to the Bacillus sp. Strain L7 had the highest capacity of producing filter paperlyase, carboxymethyl cellulase, β-glucosidase and pectinase, which reached 1.84, 0.79, 1.6 and 1.24 U/mL, respectively. All four strains could survive in the gastrointestinal environment, exhibiting strong antibacterial and co-aggregation properties, non-hemolytic activity, and antibiotic sensitivity, indicating of great probiotic characteristics and safety. Besides, L7 demonstrated the best fermentation effect on XHCP. The bound flavonoid components of XHCP were effectively converted into free form and released, especially hesperidin, nobiletin and tangeretin, increasing 34.8%, 93.7% and 102.7%, respectively, compared to the unfermented XHCP. Additionally, L7 fermented XHCP showed stronger antioxidant activity, which was closely related to its higher naringenin and hesperetin content. The results of this study can provide valuable references for the development of healthy products of XHCP and the establishment of accelerated aging techniques.